UNAIDS : the First Ten Years. - UNAIDS (World Health Organization, 2008)
This is the history of a relatively young organization-UNAIDS, launched in 1996 to strengthen the way in which the United Nations (UN) was responding to AIDS, one of the worst pandemics the world has ever known. By 1996, some 15 years since a few cases of the new condition were first reported in a scientific publication, over four million people had died from AIDS, several million were living with HIV and the future predictions were dire. This book relates the struggles and achievements of the institution, and the contribution it has made to the progress, however slow and faltering at times, i.